2014
DOI: 10.1007/s00418-014-1236-8
|View full text |Cite
|
Sign up to set email alerts
|

Caveolins redistribute in uterine epithelial cells during early pregnancy in the rat: An epithelial polarisation strategy?

Abstract: At the time of implantation, uterine luminal epithelial cells undergo a dramatic change in all plasma membrane domains. Changes in the basolateral plasma membrane at the time of implantation include progression from smooth to highly tortuous, as well as a loss of integrin-based focal adhesions. Another aspect of the basolateral plasma membrane that has not been studied in uterine epithelial cells are caveolae, which are omega-shaped invaginations of the plasma membrane known to be involved in endocytosis and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The additional nuclear and lateral localization suggests a dual role for Desmoglein‐2 in both cell signaling and cell adhesion during and after implantation in T. vulpecula (Bonné et al, ; Schlegel et al, ). This conclusion is supported by localization of Desmoglein‐2 to the apical plasma membrane during pregnancy in T. vulpecula , as apical binding of desmogleins can trigger intracellular signaling pathways (Schlegel et al, ) that may relate to maintenance of epithelial cell polarity (Madawala, Dowland, Poon, Lindsay, & Murphy, ). Apical localization of Desmoglein‐2 can also stabilize epithelial cells against apoptosis (Nava et al, ; Singh & Aplin, ), as demonstrated in intestinal epithelia following inflammation by consequent loss of cell‐cell adhesion (Nava et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…The additional nuclear and lateral localization suggests a dual role for Desmoglein‐2 in both cell signaling and cell adhesion during and after implantation in T. vulpecula (Bonné et al, ; Schlegel et al, ). This conclusion is supported by localization of Desmoglein‐2 to the apical plasma membrane during pregnancy in T. vulpecula , as apical binding of desmogleins can trigger intracellular signaling pathways (Schlegel et al, ) that may relate to maintenance of epithelial cell polarity (Madawala, Dowland, Poon, Lindsay, & Murphy, ). Apical localization of Desmoglein‐2 can also stabilize epithelial cells against apoptosis (Nava et al, ; Singh & Aplin, ), as demonstrated in intestinal epithelia following inflammation by consequent loss of cell‐cell adhesion (Nava et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…The loss of focal adhesions at the time of implantation is a key component of the plasma membrane transformation. [14][15][16] The internalization of these adhesive complexes is thought to be driven by caveolae in UECs 18 and allows these cells to be removed to facilitate blastocyst penetration. 26,27 This study has examined prominin-2 in UECs and the potential involvement of this protein in the regulation of caveolae and it demonstrates for the first time that prominin-2 is present in the rat uterus, where it is restricted to the luminal and glandular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…For each sample, at least 30 images were taken at 50 000Â magnification and caveolae were counted in a single-blind study, where images selected were counted by an individual who was blinded to treatment status, as previously described by Madawala et al 18 Basal plasma membranes from each treatment group were measured using ImageJ software (version 1.6.0_20), and morphological caveolae (50-100 nm) with a neck connecting them to the basal plasma membrane were counted. Smooth, uncoated vesicles within the same size range and within 100 nm of the basal plasma membrane were also counted.…”
Section: Morphometrymentioning
confidence: 99%
See 2 more Smart Citations